Sensitivity of Annual Weeds Against Metolachlor + Bensulfuron - Methyl Herbicide in Transplanted Rice - Bhuiyan, MKA; Mahbub, MM; Baki, MZI (Bangladesh Agronomy Journal, 2018)
Field trials were conducted at Bangladesh Rice Research Institute (BRRI), Gazipur during aman, 2014 and boro, 2014-15 to evaluate the efficacy of metolachlor + bensulfuron methyl 20% WP on weed suppression of transplanted rice. Metolachlor + bensulfuron methyl 20% WP @ 150, 190 and 230 g ha-1 were applied and pyrazosulfuran ethyl @ 125 g ha-1, weed free and unweeded control were the treatment variables. Visual observations indicated that this herbicide possesses high selectivity and not toxic to rice plants. The results revealed that the major weed flora associated with the transplanted rice was mainly comprised of two grasses, two sedges and three broadleaf in aman and two grasses, two sedges and two broadleaf in boro season. The most dominant weeds were Cyperus difformis, Echinochloa crus-galli, Scirpus maritimus and Monochoria vaginalis in both the growing seasons. Application of metolachlor + bensulfuron methyl 20% WP @ 190 g ha-1 was most effective to suppress weeds in both the seasons resulting in increased grain yield more than 40% as compared to unweeded control. Therefore, metolachlor + bensulfuron methyl 20% WP@ 190 g ha-1applied at one to two leaf stage of weed effectively controls the weed infestation in transplanted rice. Bangladesh Agron. J. 2018, 21(1): 61-70